The Effectiveness of Speechace Application in Enhancing EFL Learners' Speaking Skills: A Quasi-Experimental Study - Lia Tazkia Qulbi; Wildan Isna Asyhar; Erwin Hari Kurniawan (LingPoet: Journal of Linguistics and Literary Research, 2026)
The pedagogical transformation of English language teaching in the digital era is characterized by the utilization of Artificial Intelligence (AI) and Automatic Speech Recognition (ASR). This study aims to evaluate the effectiveness of the Speechace application in enhancing students' speaking competence at Mr.Bob English Course through a quasi-experimental design. A total of 33 respondents were involved and divided into experimental and control groups to measure their pronunciation accuracy and fluency levels. Data collection instruments included oral performance tests (pre-test and post-test) and a learner autonomy questionnaire. The results of the Independent Samples T-test analysis showed a significant difference in mean scores between the two groups (t = 3.88; p < .001), with the experimental group demonstrating superior performance. These findings confirm that AI-based tools are capable of providing an autonomous and effective practice environment, while simultaneously serving as a solution to the limitations of personalized feedback within the context of EFL learning in Indonesia.